Fullerenol-cytotoxic conjugates for cancer chemotherapy - Chaudhuri, Padmaparna; Paraskar, Abhimanyu; Soni, Shivani; Mashelkar, Raghunath Anant; Sengupta, Shiladitya (ACS Nano, 2009)
In the present study, we report the novel application of polyhydroxylated fullerenes (fullerenols) in cancer drug delivery. The facile synthetic procedure for generating multiple hydroxyl groups on the fullerene cage offers scope for high drug loading in addition to conferring hydrophilicity. Doxorubicin, a first line cancer chemotherapeutic, was conjugated to fullerenols through a carbamate linker, achieving ultrahigh loading efficiency. The drug-fullerenol conjugate was found to be relatively stable in phosphate buffer saline but temporally released the active drug when incubated with tumor cell lysate. The fullerenol-doxorubicin conjugate suppressed the proliferation of cancer cell-lines in vitro through a G2-M cell cycle block, resulting in apoptosis. Furthermore, in an in vivo murine tumor model, fullerenol-doxorubicin exhibited Comparable antitumor efficacy as free drug without the systemic toxicity of free doxorubicin. Additionally, we demonstrate that the fullerenol platform can be extended to other chemotherapeutic agents, such as the slightly water-soluble cisplatin, and can emerge as a new paradigm in the management of cancer.
Keywords: chemotherapy; doxorubicin; drug delivery; fullerenol; nanoparticle

Nanoparticle-mediated targeting of MAPK signaling predisposes tumor to chemotherapy - Basu, Sudipta; Harfouche, Rania; Soni, Shivani; Chimote, Geetanjali; Mashelkar, Raghunath Anant; Sengupta, Shiladitya (Proceedings of the National Academy of Sciences of the United States of America, 2009)
The MAPK signal transduction cascade is dysregulated in a majority of human tumors. Here we report that a nanoparticle-mediated targeting of this pathway can optimize cancer chemotherapy. We engineered nanoparticles from a unique hexadentate-polyD, L-lactic acid-co-glycolic acid polymer chemically conjugated to PD98059, a selective MAPK inhibitor. The nanoparticles are taken up by cancer cells through endocytosis and demonstrate sustained release of the active agent, resulting in the inhibition of phosphorylation of downstream extracellular signal regulated kinase. We demonstrate that nanoparticle-mediated targeting of MAPK inhibits the proliferation of melanoma and lung carcinoma cells and induces apoptosis in vitro. Administration of the PD98059-nanoparticles in melanoma-bearing mice inhibits tumor growth and enhances the antitumor efficacy of cisplatin chemotherapy. Our study shows the nanoparticle-mediated delivery of signal transduction inhibitors can emerge as a unique paradigm in cancer chemotherapy.
Keywords: cancer; Signal transduction

Coupling growth-factor engineering with nanotechnology for therapeutic angiogenesis - Roy, Rituparna Sinha; Soni, Shivani; Harfouche, Rania; Vasudevan, Pooja R.; Holmes, Oliver; de Jonge, Hugo; Rowe, Arthur; Paraskar, Abhimanyu; Hentschel, Dirk M.; Chirgadze, Dimitri; Blundell, Tom L.; Gherardi, Ermanno; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Therapeutic angiogenesis is an emerging paradigm for the management of ischemic pathologies. Proangiogenic Therapy is limited, however, by the current inability to deliver angiogenic factors in a sustained manner at the site of pathology. In this study, we investigated a unique nonglycosylated active fragment of hepatocyte growth factor/scatter factor, 1K1, which acts as a potent angiogenic agent in vitro and in a zebrafish embryo and a murine matrigel implant model. Furthermore, we demonstrate that nanoformulating 1K1 for sustained release temporally alters downstream signaling through the mitogen activated protein kinase pathway, and amplifies the angiogenic outcome. Merging protein engineering and nanotechnology offers exciting possibilities for the treatment of ischemic disease, and furthermore allows the selective targeting of downstream signaling pathways, which translates into discrete phenotypes.
Keywords: cardiovascular disease; HGF/SF; ischemic disease; nanoparticle; protein engineering

Harnessing structure-activity relationship to engineer a cisplatin nanoparticle for enhanced antitumor efficacy - Paraskar, Abhimanyu S.; Soni, Shivani; Chin, Kenneth T.; Chaudhuri, Padmaparna; Muto, Katherine W.; Berkowitz, Julia; Handlogten, Michael W.; Alves, Nathan J.; Bilgicer, Basar; Dinulescu, Daniela M.; Mashelkar, Raghunath Anant; Sengupta, Shiladitya (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Cisplatin is a first line chemotherapy for most types of cancer. However, its use is dose-limited due to severe nephrotoxicity. Here we report the rational engineering of a novel nanoplatinate inspired by the mechanisms underlying cisplatin bioactivation. We engineered a novel polymer, glucosamine-functionalized polyisobutylene-maleic acid, where platinum (Pt) can be complexed to the monomeric units using a monocarboxylato and an O –> Pt coordinate bond. We show that at a unique platinum to polymer ratio, this complex self-assembles into a nanoparticle, which releases cisplatin in a pH-dependent manner. The nanoparticles are rapidly internalized into the endolysosomal compartment of cancer cells, and exhibit an IC50 (4.25 + 0.16 mu M) comparable to that of free cisplatin (3.87 +/- 0.37 mu M), and superior to carboplatin (14.75 +/- 0.38 mu M). The nanoparticles exhibited significantly improved antitumor efficacy in terms of tumor growth delay in breast and lung cancers and tumor regression in a K-ras(LSL/+)/Pten(fl/fl) ovarian cancer model. Furthermore, the nanoparticle treatment resulted in reduced systemic and nephrotoxicity, validated by decreased biodistribution of platinum to the kidney as quantified using inductively coupled plasma spectroscopy. Given the universal need for a better platinate, we anticipate this coupling of nanotechnology and structure-activity relationship to rationally reengineer cisplatin could have a major impact globally in the clinical treatment of cancer.
Keywords: cancer; chemotherapy; nanomedicine

Cholesterol-tethered platinum II-based supramolecular nanoparticle increases antitumor efficacy and reduces nephrotoxicity - Sengupta, Poulomi; Basu, Sudipta; Soni, Shivani; Pandey, Ambarish; Roy, Bhaskar; Oh, Michael S.; Chin, Kenneth T.; Paraskar, Abhimanyu S.; Sarangi, Sasmit; Connor, Yamicia; Sabbisetti, Venkata S.; Kopparam, Jawahar; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Nanoscale drug delivery vehicles have been harnessed extensively as carriers for cancer chemotherapeutics. However, traditional pharmaceutical approaches for nanoformulation have been a challenge with molecules that exhibit incompatible physicochemical properties, such as platinum-based chemotherapeutics. Here we propose a paradigm based on rational design of active molecules that facilitate supramolecular assembly in the nanoscale dimension. Using cisplatin as a template, we describe the synthesis of a unique platinum (II) tethered to a cholesterol backbone via a unique monocarboxylato and O -> Pt coordination environment that facilitates nanoparticle assembly with a fixed ratio of phosphatidylcholine and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine- N-[amino (polyethylene glycol)-2000]. The nanoparticles formed exhibit lower IC50 values compared with carboplatin or cisplatin in vitro, and are active in cisplatin-resistant conditions. Additionally, the nanoparticles exhibit significantly enhanced in vivo antitumor efficacy in murine 4T1 breast cancer and in K-Ras(LSL/+/)Pten(fl/fl) ovarian cancer models with decreased systemic- and nephro-toxicity. Our results indicate that integrating rational drug design and supramolecular nanochemistry can emerge as a powerful strategy for drug development. Furthermore, given that platinum-based chemotherapeutics form the frontline therapy for a broad range of cancers, the increased efficacy and toxicity profile indicate the constructed nanostructure could translate into a nextgeneration platinum-based agent in the clinics.
Keywords: chemotherapy; nanomedicine